Effect Of Work Environment And Work Discipline On The Performance Of Spkt Unit Members (Integrated Police Service Center) Sungai Penuh Polsek With Work Motivation As An Intervening Variable - Jullyantiara Dwi Putri (Jurnal Pembangunan Berkelanjutan, 2020)
The purpose of research it is to know the influence of the environment of work and discipline of work against the performance of members of Unit IFMS (Central Services Police Integrated) Sungai Penuh Police with motivation work as variable intervening . This research is motivated by a work environment that is quite extensive and complex, working hours are not stable, so it requires high attention, level of discipline is still not evenly distributed, charging absences are rare, motivation to work less, supported infrastructure that it is still lacking, the performance of the agency and Members of the Sungai Penuh Police Sector SPKT are still low and unstable from year to year. The research method with a quantitative approach with the path analysis method. Data collection techniques with questionnaires, observation and interviews . Respondents of this study were 42 members of the SPKT (Integrated Police Service Center) Sungai Penuh Police Station. Method of withdrawal of samples using methods of total sampling where the entire population in the study used a sample. Hypothesis testing is calculated by the SPSS program version 24.0. The results of this study found that the work environment has a significant effect on motivation, work discipline has no significant effect on motivation, meaning that the higher the influence of work discipline does not affect motivation, the work environment has a significant effect on performance, work discipline has a significant effect on performance, motivation has a significant effect on performance, indirectly the work environment through motivation has a significant influence on performance, and indirectly work discipline through motivation has an insignificant effect on the performance of the Sungai Penuh police station SPKT member.